Noncontact monitoring of heart rate responses to taste stimuli using a video camera - Masnani Bt Mohamed; Makoto Yoshizawa; Norihiro Sugita; Shunsuke Yamaki; Kei Ichiji (Institute of Advanced Engineering and Science, 2020)
Pleasant or unpleasant feeling stimulated by taste usually expressed to describe the acceptance or rejection of food and beverages intake by a human. Since it stimulates the emotional reactions, therefore it also induces other response such as heart rate variations. Traditional sensory tools used only subjective measurement such as self-report, to estimate the feeling of tasting. This method sometimes failed to show some differences between the pleasant and unpleasant type of feelings unconsciously. Previous unconscious measurement methods used the intrusive technique by placing some sensors in contact with the body, which may affect the results of sensory analysis. This study was conducted to avoid the effects of using contact sensors and validate the contact-less method of monitoring heart rate due to emotional changes by extracting plethysmographic signal from the green component of the video images. The videos were recorded while the subject responded to pleasant, unpleasant and neutral stimuli. The findings indicated that the heart rate was significantly related to taste stimuli that also reflected the subjective feelings. The unpleasant-taste influenced heart rate to increase more compared to pleasant-taste and neutral-taste. This proposed approach can be used to remotely detect the feeling/emotion that not overtly express through facial expression, speech or gestures.